HEALTH-PRESERVING COMPETENCE AS A KEY COMPONENT OF FUTURE PSYCHOLOGISTS’ PROFESSIONAL TRAINING (Physical Culture and Sport: Scientific Perspective, 2024)
Health-preserving competence is a crucial element of the professional training of future psychologists. It equips them with the ability not only to maintain and support their own physical, mental, and emotional health but also to effectively assist others in achieving psychological well-being. This competence has gained particular importance in the face of modern challenges, including rising stress levels, emotional burnout, and the growing prevalence of psychological issues among the population.This article examines the concept of "health-preserving competence" and identifies its core components. These include knowledge about health preservation methods, practical skills for their implementation, emotional resilience, self-regulation, and reflective abilities. Special attention is given to its role in the professional development of psychologists who work in complex social and psychological environments. The emphasis is placed on the necessity of developing self-preservation skills in professional practice, preventing emotional burnout, and fostering a harmonious working environment.The study also highlights the significance of health-preserving competence in the context of professional ethics. A psychologist should serve as a role model of a healthy lifestyle and demonstrate self-help capabilities to effectively promote the well-being of their clients. The integration of this competence into educational programs, training, and practical exercises during the preparation of future professionals is analyzed.It is established that health-preserving competence represents an integrative quality of personality. It encompasses a set of knowledge, skills, and abilities essential for maintaining, preserving, and enhancing not only one’s own health but also the health of others. This multifaceted competence ensures that psychologists are better equipped to navigate the demands of their profession and support their clients’ mental health effectively.
Keywords: health; competence; future psychologists; professional training